The impact of stopping and starting indoor residual spraying on malaria burden in Uganda - Jane F. Namuganga (Nature Portfolio, 2021)
Indoor residual spraying (IRS) of insecticide is one of the primary malaria vector control initiatives, but implementation is limited. Here, the authors show that discontinuation of IRS in Uganda was associated with increased malaria incidence, and introduction of IRS was associated with decreased incidence.